2017
DOI: 10.1038/s41598-017-10752-w
|View full text |Cite
|
Sign up to set email alerts
|

Forensic age prediction for saliva samples using methylation-sensitive high resolution melting: exploratory application for cigarette butts

Abstract: There is high demand for forensic age prediction in actual crime investigations. In this study, a novel age prediction model for saliva samples using methylation-sensitive high resolution melting (MS-HRM) was developed. The methylation profiles of ELOVL2 and EDARADD showed high correlations with age and were used to predict age with support vector regression. ELOVL2 was first reported as an age predictive marker for saliva samples. The prediction model showed high accuracy with a mean absolute deviation (MAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 45 publications
0
50
3
1
Order By: Relevance
“…The prediction of skin color from DNA has also been reported ( Chaitanya et al, 2018 ) and DNA methylation has been demonstrated as a useful predictor of age. Age prediction using methylation techniques have indicated a mean absolute deviation of 5–8 years ( Xu et al, 2015 ; Bocklandt et al, 2011 ; Hamano et al, 2017 )…”
Section: Understanding the Etiology Of Craniofacial Anomaliesmentioning
confidence: 99%
“…The prediction of skin color from DNA has also been reported ( Chaitanya et al, 2018 ) and DNA methylation has been demonstrated as a useful predictor of age. Age prediction using methylation techniques have indicated a mean absolute deviation of 5–8 years ( Xu et al, 2015 ; Bocklandt et al, 2011 ; Hamano et al, 2017 )…”
Section: Understanding the Etiology Of Craniofacial Anomaliesmentioning
confidence: 99%
“…Different array‐ and sequence‐based techniques for measuring genome‐wide DNA methylation patterns have been developed . Multiple research groups have identified CpG sites that were significantly correlated with age by using different tissue samples, such as saliva , skin , semen , and whole blood/leukocytes in female twins or children . Furthermore, different approaches were carried out to detect methylation states.…”
mentioning
confidence: 99%
“…Dans une approche plus simple, Hamano et al [57] ont mis au point une méthode HRM sensible à la méthylation basée sur les promoteurs de deux gènes associés à l'âge précédemment décrits (ELOVL2 et EDARADD) et ont testé près de 250 échantillons de salive et de mégots de cigarettes. Les auteurs ont réussi à prédire l'âge avec un MAD de 6,25 ans dans la salive et de 7,65 ans sur les mégots de cigarettes.…”
Section: Estimation De L'âge Dans Les Tissusunclassified